PHYTOPLANKTON COMPOSITION OF SAWA LAKE, IRAQ. - HASSAN, FIKRAT M.; AL-SAADI, HUSSAIN A. AL-SAADI; ALKAM, FOAD M. (Iraqi Journal of Aquaculture, 2022)
The phytoplankton composition of Sawa Lake was studied monthly for 18 months, from October 1999 to March 2001. A phytoplankton net (20 ) was used to collect phytoplankton samples. A total of 51 algal taxa was identified belong to diatoms (Bacillariophyceae), blue greens (Cyanophyceae), green algae (Chlorophyceae) and euglenoids (Euglenophyceae). Diatoms were dominated in species number (64.7%) and total cell number (68.6%) followed by blue greens (23.5%) and (15.5%), and the green (7.8%) and (14.5%) respectively. Bimodal seasonal peaks of chlorophyll-a and phytoplankton population were observed in the lake.